Microwave-assisted synthesis and bioevaluation of new sulfonamides. (1st January 2017) - Gul, Halise Inci; Yamali, Cem; Yesilyurt, Fatma; Sakagami, Hiroshi; Kucukoglu, Kaan; Gulcin, Ilhami; Gul, Mustafa; Supuran, Claudiu T.
Abstract: In this study, 4-[5-(4-hydroxyphenyl)-3-aryl-4, 5-dihydro-1 H -pyrazol-1-yl]benzenesulfonamide derivatives (8-14 ) were synthesized for the first time by microwave irradiation and their chemical structures were confirmed by 1 H NMR, 13 C NMR and HRMS. Cytotoxic activities and inhibitory effects on carbonic anhydrase I and II isoenzymes of the compounds were investigated. The compounds9 (PSE = 4.2), 12 (PSE = 4.1) and13 (PSE = 3.9) with the highest potency selectivity expression (PSE) values in cytotoxicity experiments and the compounds13 ( Ki  = 3.73 ± 0.91 nM toward hCA I) and14 ( Ki  = 3.85 ± 0.57 nM toward hCA II) with the lowest Ki values in CA inhibition studies can be considered as leader compounds for further studies.